2010
DOI: 10.1128/jb.01049-09
|View full text |Cite
|
Sign up to set email alerts
|

The Aromatic Ring of Phenylalanine 334 Is Essential for Oligomerization ofVibrio vulnificusHemolysin

Abstract: Vibrio vulnificus hemolysin (VVH) is thought to be a member of the cholesterol-dependent cytolysin (CDC) family of pore-forming toxins. To date, the structure-function relationships of CDCs produced by Gramnegative bacteria remain largely unknown. We show here that the aromatic ring of phenylalanine residue conserved in Vibrionaceae hemolysins is essential for oligomerization of VVH. We generated the VVH mutants; substituted Phe 334 for Ile (F334I), Ala (F334A), Tyr (F334Y), or Trp (F334W); and tested their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…The third transition involves a 35°rigid-body rotation of the β-trefoil lectin domain around the loop connecting it to the cytolytic domain. The short helical turn that precedes the β-trefoil linker is anchored within the cytolysin domain by a phenylalanine residue (F455) that is necessary for oligomerization in the related Vibrio vulnificus hemolysin (33). The fourth transition is a movement of the loop that cradles the prestem in the water-soluble structure (residues 191-203) through hydrophobic side-chain interactions (notably L192, Y194, L307, and A309) and backbone hydrogen bonds involving G291 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The third transition involves a 35°rigid-body rotation of the β-trefoil lectin domain around the loop connecting it to the cytolytic domain. The short helical turn that precedes the β-trefoil linker is anchored within the cytolysin domain by a phenylalanine residue (F455) that is necessary for oligomerization in the related Vibrio vulnificus hemolysin (33). The fourth transition is a movement of the loop that cradles the prestem in the water-soluble structure (residues 191-203) through hydrophobic side-chain interactions (notably L192, Y194, L307, and A309) and backbone hydrogen bonds involving G291 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the VVH-lectin domain can recognize a carbohydrate chain. In fact, Kashimoto et al have suggested that the VVH-lectin domain may be required to bind to cellular membranes [6]. In this study, MβCD decreased the binding efficiency of VVH to CHO cells (Fig.…”
mentioning
confidence: 46%
“…Vibrio vulnificus hemolysin (VVH) is a possible virulence factor which is produced by V. vulnificus [3,12]. This toxin has been reported to cause cytolysis of various eukaryotic cells, as well as erythrocytes [6,12,20]. With regard to the hemolytic or cytotoxic mechanism (s) of VVH, it has been reported that VVH monomer binds to cellular membranes to form oligomers, and that these oligomers form ion-permeable pores which exert hemolysis or cytotoxicity via colloid osmotic shock [8,19].…”
mentioning
confidence: 99%
“…This species commonly produces a hemolytic/cytolytic toxin termed V. vulnificus hemolysin (VVH) (Shinoda et al, 1985;Miyoshi et al, 1993), which has been reported to 10 cause cytolysis of various eukaryotic cells, as well as erythrocytes (Yamanaka et al, 1990;Miyoshi et al, 1993;Kashimoto at al., 2010). For hemolysis, the toxin binds specifically to cholesterol and is subsequently assembled on the membrane to form an oligomer (Yamanaka et al, 1987;Kim and Kim, 2002).…”
Section: Introductionmentioning
confidence: 99%